Fortifying The Data Link Layer: An Analysis of Security Concerns (American Journal of Multidisciplinary Research and Innovation, 2025)
Network operations are separated into seven tiers by a conceptual model of networking known as the Open Systems Interconnect Model (OSI). This explains the way layers communicate with one another.This paradigm explains the way layers communicate with one another. I discuss common Data link layer attacks in this Research, along with possible defenses, and introduce new attacks.The data link layer is regarded as an extremely vulnerable point in a secure network Because each layer operates independently of the others; if the data is compromised at the Data link layer, it cannot be discovered at higher layers. The use of various attack tools by an attacker to exploit a network is described. My findings demonstrate how effective these attacks may be when a network administrator neglects to install suitable security at the Data link layer of the OSI model.